2023
DOI: 10.1002/ptr.7963
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect of luteolin proven by patient‐derived organoids of gastric cancer

Abstract: Luteolin (Lut) has been shown to inhibit gastric cancer (GC); however, its efficacy compared to other clinical drugs has not been examined in human samples. This study aimed to elucidate the antitumor activity of Lut in GC patient‐derived organoids (PDOs). PDOs were established from GC cancer tissues, and the characterization of tissues and PDOs was performed using whole‐exome sequencing. Drug sensitivity tests were performed by treating PDOs with Lut, norcantharidin (NCTD), and carboplatin (CP). RNA sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Its efficacy, low toxicity, and good safety make it a prospective drug for the treatment of malignant tumors [ 25 ]. Besides, In vitro and in vivo studies have shown that luteolin can inhibit GC through a variety of mechanisms, such as regulating Notch, MAPK, PI3K and other signal pathways, inducing G2/M cell cycle arrest and apoptosis [ 26 , 27 ]. Kaempferol, as another active ingredient of XSLJZT, has anti-inflammatory and anti-cancer biological activities.…”
Section: Discussionmentioning
confidence: 99%
“…Its efficacy, low toxicity, and good safety make it a prospective drug for the treatment of malignant tumors [ 25 ]. Besides, In vitro and in vivo studies have shown that luteolin can inhibit GC through a variety of mechanisms, such as regulating Notch, MAPK, PI3K and other signal pathways, inducing G2/M cell cycle arrest and apoptosis [ 26 , 27 ]. Kaempferol, as another active ingredient of XSLJZT, has anti-inflammatory and anti-cancer biological activities.…”
Section: Discussionmentioning
confidence: 99%